Guillain‐Barré syndrome associated with CASPR2 antibodies: two paediatric cases. Issue 3 (September 2014) - Rosch, Richard E.; Bamford, Alasdair; Hacohen, Yael; Wraige, Elizabeth; Vincent, Angela; Mewasingh, Leena; Lim, Ming
Abstract The pathogenesis of Guillain‐Barré syndrome (GBS) is considered to be, at least in part, mediated by autoantibodies directed against neuronal antigens. Antibodies to contactin‐associated protein‐like 2 (CASPR2), part of the voltage‐gated potassium channel complex (VGKC‐complex), are associated with neurological disease predominantly affecting the peripheral nervous system but are not known to be associated with GBS. We report two cases of ganglioside antibody‐negative paediatric GBS associated with CASPR2 antibodies. Both patients made a complete clinical recovery. The tissue distribution and function of CASPR2 make it a biologically plausible autoimmune target in GBS and its clinical relevance in GBS should be determined in further studies.